Role of Gastric Microorganisms Other than Helicobacter pylori in the Development and Treatment of Gastric Diseases. (14th March 2022) - Duan, Xiaoyan; Chen, Ping; Xu, Xiaoxia; Han, Meiling; Li, Jianbo
Abstract : The microenvironment in the stomach is different from other digestive tracts, mainly because of the secretion of gastric acid and digestive enzymes, bile reflux, special mucus barrier, gastric peristalsis, and so on, which all contribute to the formation of antibacterial environment. Microecological disorders can lead to gastric immune disorders or lead to the decrease of dominant bacteria and the increase of the abundance and virulence of pathogenic microorganisms and then promote the occurrence of diseases. The body performs its immune function through innate and adaptive immunity and maintains microbial balance through the mechanism of immune homeostasis. Microecological imbalance can lead to the invasion of pathogenic microorganisms and damage mucosal barrier and immune system. The coexistence of gastric microorganisms (including viruses and fungi) may play a synergistic or antagonistic role in the pathogenesis of gastric diseases. Probiotics have the ability to compete with intestinal pathogens, increase the secretion of immunoglobulin A (IgA), stimulate the production of mucin, bacteriocin, and lactic acid, regulate the expression and secretion of cytokines, and regulate the growth of microbiota, which all have beneficial effects on the host microbial environment. At present, most studies focused on Helicobacter pylori, ignoring other stomach microbes and the overall stomach microecology. So, in this article, we reviewed advances in human gastric microecology, the relationship between gastric microecology and immunity or gastric diseases, and the treatment of probiotics in gastric diseases, in order to explore new area for further study of gastric microorganisms and treatment of gastric diseases.